Bibliometric Analysis of Islamic Psychology - Loso Judijanto (West Science Islamic Studies, 2026)
Islamic Psychology has emerged as an interdisciplinary field that integrates psychological science with Islamic values, spirituality, cultural perspectives, and approaches to human well-being. Despite its growing academic attention, the global development patterns, intellectual structures, and emerging research directions of Islamic Psychology remain insufficiently explored. This study aims to examine the evolution of Islamic Psychology research through a bibliometric analysis approach. Data were retrieved from the Scopus database using relevant keywords related to Islamic Psychology, Muslim psychology, Islamic psychotherapy, and Islamic mental health. The collected publications were analyzed using bibliometric techniques, including publication trend analysis, citation analysis, co-authorship analysis, country collaboration analysis, keyword co-occurrence analysis, and density visualization through VOSviewer. The findings indicate that Islamic Psychology research has experienced continuous development, supported by contributions from various countries and international scholarly networks. The intellectual structure of the field demonstrates strong connections between Islamic concepts, psychological theories, spirituality, cultural factors, and mental health studies. The keyword analysis reveals a transformation from theoretical discussions on religion, Islamic perspectives, and cultural identity toward more empirical investigations involving depression, mental health, psychological assessment, and evidence-based interventions. This study highlights that Islamic Psychology has developed into a globally recognized interdisciplinary research field that bridges Islamic intellectual traditions with contemporary psychological approaches. The findings provide valuable insights for future scholars to further investigate Islamic psychotherapy, spiritual well-being, culturally sensitive psychological interventions, and new theoretical frameworks integrating Islamic perspectives with modern psychology.